Principais métricas utilizadas para monitorar a carga musculoesquelética e psicofisiológica no voleibol indoor e no voleibol de praia - Silva, Geovani Messias da (2022)
Team sports require an optimal interactional behavior between players of the same team and players of the opposing team, which characterizes a social microsystem. This complex dynamic derived from physical, mental and environmental demands is a key part in the gain of individual and collective performance, and in reducing the risk of injury. In indoor and beach volleyball this relationship becomes closer due to the number of athletes and the speed of the match, maintaining the tactical factor depends on the synchronized interaction of the athletes within this social microsystem. This needs to preserve and improve the team's performance entails the need for a system to monitor the demands supported by the athletes. This system can be divided into the training organization, quality and quantity, under the term external load; and the psychophysiological bases, collectively classified as internal load. However, even though load control is widely researched, some information is still not available in the literature. Given the specificity of internal and external load measurement in the context of indoor and beach volleyball, it is essential to know which and how much each measure is being used in the two sports. We aimed to describe the load control measures used in indoor and beach volleyball. We searched online databases such as MEDLINE, Scopus, SportDiscus, and Web of Science through July 2022. We found 597 records and discarded: 222 duplicate records, 135 due to abstract content, and 48 not retrieved. We excluded 94 articles based on eligibility criteria. After screening, 98 articles were included. We concluded that most studies in beach and indoor volleyball used RPE, recovery and wellness monitoring, and heart rate to measure internal load. In beach volleyball mainly jump height was used to measure external load. In beach volleyball used jump height, number of jumps, and speed and agility as the main methods to measure external load. Given the above in our results, it is important to see how the methods are being used in daily practice. Future field research can verify how the main metrics are used daily by the staff, comparing with the literature recommendations.